Pertumbuhan Eucalyptus urophylla St Blake Di Kabupaten Humbang Hasundutan (Growth of Eucalyptus urophylla St Blake in Humbang Hasundutan District) - Benteng Sihombing; Rozalina Rozalina (Median : Jurnal Ilmu Ilmu Eksakta, 2022)
The demanded of raw matters wood of pulp/ papers industries in Indonesia every year has been increased. The government was spruced wood production by man made forest society. In Humbang Hasundutan district, the implementation man made forest society was developed by pattern of foster father. The aims of this reasearcing are to know the wood potency of Eucalyptus urophylla St Blake in man made forest society in Humbang Hasundutan district. The result of Eucalyptus urophylla St Blake research in 3 different sites are knowed that there are differencing in growth and if it comparin to the grotwh of Eucalyptus urophylla St Blake on Toba Pulp Lestari Limited Corporate area. Based on data analysis show there is a indicated the growth of Eucalyptus urophylla St. Blake in Toba Pulp Lestari Limited Corporate area best growing than all site in man made forest society area in Humbang Hasundutan district. The wood potency in 3 site man made forest society area in Humbang Hasundutan district has smaller than wood potency of Toba Pulp Lestari Limited Corporate area.